KOMBINASI PIJAT PUNGGUNG DAN ENDORPHIN TERHADAP PRODUKSI ASI PADA IBU POST PARTUM - Dewi, Adinda Putri Sari; Indrayani, Eni; Khanifah, Rina (LPPM STIKES MUHAMMADIYAH GOMBONG, 2017)
The high infant mortality rate in Indonesia can be prevented through early breastfeeding (ASI) and exclusive breastfeeding.Combination Back Massage and Endorphin is one of interventions that hopped to help post partum mothers in increasing breast milk production and to support breastfeed for the newborn. To find out the effectiveness of combination of back massage and endorphin to breast milk production in postpartum mothers. The study used quasi experiment using post test only design with control group. The samples were taken using consecutive sampling with a total of 22 samples for each group (intervention and control). Bivariat analysis used chi square with a significance level of p <0.05. The results indicate that there is a difference in milk production between the intervention and the control groups with an OR of 0,2 (95% CI: 0,060 to 0,770). Parity and frequency of breastfeeding have significant correlation with breast milk production. Mother’s age, parity, work, obesity, and frequency of breastfeeding have no significant correlation with breast milk production. The conclusions of this research are combination of back massage and endorphin to breast milk production.